Seed germination response of various cannabis landraces to polyethylene glycol-induced drought stress - Langa, Sabeliwe; Magwaza, Lembe Samukelo; Mditshwa, Asanda; Tesfay, Samson Zeray (Springer, 2026)
This study examined the impact of PEG-induced water stress on seed germination of eight cannabis landraces, namely, ‘B1’, ‘B2’, ‘B3’, ‘H1’, ‘L1’, ‘L2’, ‘M1’ and ‘M2’, sourced from four distinct regions of KwaZulu-Natal, South Africa: Bergville (B), Hammersdale (H), Ladysmith (L), and Msinga (M). Drought stress was induced using PEG 8000 (0, − 0.2, − 0.4, − 0.6, − 0.8, and − 1.0 MPa) in laboratory and greenhouse conditions. Germination percentage (GP), germination rate index (GRI), germination stress tolerance index (GSTI), seedling length, and seed vigour index (SVI) were recorded. In general, there were statistically significant differences (p < 0.05) among landraces, PEG treatments, and their interactions for germination characteristics in both greenhouse and laboratory environments. However, the interaction between landraces and PEG treatments did not show statistical differences (p > 0.05) in germination percentage under greenhouse conditions. The germination characteristics were reduced under PEG treatments relative to the control. Under laboratory conditions, germination declined progressively with increasing PEG concentration. Complete inhibition of GP occurred at − 1.0 MPa in landraces ‘M1’ and ‘L1’. However, at this stress level, ‘L2’ had the highest GP of 58.67% and GRI of 1.78 seeds/day, while ‘B1’ exhibited the highest GSTI at 18.41%. In corresponding greenhouse experiment at − 1.0 MPa, ‘H1’ maintained the highest GP of 92.00%, while ‘B3’ achieved the highest GRI (5.28 seeds/day), GSTI (100.99%), seedling length (167.7 mm), and SVI (1.114). This study identified ‘L2’, ‘B1’, ‘H1’, and ‘B3’ as promising landraces for cultivation in water-limited environments and for use in breeding programs.
Keywords: Cannabis landrace; Polyethylene glycol; Germination recovery; Drought stress; 30 Agricultural, Veterinary and Food Sciences; 3004 Crop and Pasture Production; Plant Biology & Botany; 3008 Horticultural production; 3108 Plant biology